2023
DOI: 10.3390/jcm12062209
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Intracranial Pressure Monitoring

Abstract: (1) Background: Intracranial pressure (ICP) monitoring plays a key role in the treatment of patients in intensive care units, as well as during long-term surgeries and interventions. The gold standard is invasive measurement and monitoring via ventricular drainage or a parenchymal probe. In recent decades, numerous methods for non-invasive measurement have been evaluated but none have become established in routine clinical practice. The aim of this study was to reflect on the current state of research and shed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 260 publications
0
4
0
Order By: Relevance
“…Intracranial masses are one of the causes of headache. Studies report that huge masses that increase intracranial pressure change NIRS values ( 25 - 27 ). NIRS gives an idea about the size of the mass and the surgical decision in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial masses are one of the causes of headache. Studies report that huge masses that increase intracranial pressure change NIRS values ( 25 - 27 ). NIRS gives an idea about the size of the mass and the surgical decision in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…It reflects the balance between oxygen supply and demand within the distal arterial, venous, and capillary territories [24]. The majority of NIRS applications involve placing optodes over the forehead and measuring signal over the frontal lobe gray matter and watershed area of anterior and middle cerebral arteries (MCA) territory with the normal range of rSO 2 between 55-80% [15][16]. Intraoperative management guided by the use of cerebral oximetry (CeOx) was associated with a reduction in postoperative complications such as stroke, ICU and hospital length of stay, and the incidence of postoperative delirium.…”
Section: Neuromonitoring In Traumatic Brain Injurymentioning
confidence: 99%
“…CeOx has been cleared by the United States Food and Drug Administration for monitoring regional cerebral oxygen saturation [4], and cerebral deoxygenation (rSO 2 below 55%) has been shown to correlate with a variety of adverse systemic complications and multi-organ failure, for example, renal failure, overall well-being, prolonged ventilation, cortical dysfunction, cerebral hypoxia, and low cardiac output syndromes. Many studies [1,7,12,16] showed that CeOx with NIRS correlated with CPP estimation, the Glasgow Outcome Score Scale, and mortality in patients with severe TBI, and NIRS has the capability to provide an early warning of cerebral ischemia and infarction. These impacts of continuous monitoring showed the above correlations between regional cerebral saturation and systemic outcomes, and most of the intraoperative measures taken to optimize cerebral rSO 2 and oxygen delivery potentially affect systemic perfusion (e.g., alterations in PaCO 2 , cardiac output, arterial blood pressure, etc.).…”
Section: Neuromonitoring In Traumatic Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…If the blood flow volume from systemic circulation required for brain metabolism exceeds 100 mmHg, increased intracranial pressure can occur. Furthermore, if cerebral perfusion pressure is less than 60 mmHg, inadequate blood flow to the brain can cause hypoxia, impaired consciousness, and even death of brain cells [12], [13].…”
Section: Introductionmentioning
confidence: 99%